2021
DOI: 10.1186/s13072-021-00397-5
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of cattle sperm sncRNAs during maturation, from testis to ejaculated sperm

Abstract: Background During epididymal transit, spermatozoa go through several functional maturation steps, resulting from interactions with epididymal secretomes specific to each region. In particular, the sperm membrane is under constant remodeling, with sequential attachment and shedding of various molecules provided by the epididymal lumen fluid and epididymosomes, which also deliver sncRNA cargo to sperm. As a result, the payload of sperm sncRNAs changes during the transit from the epididymis caput … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 84 publications
(105 reference statements)
0
19
0
Order By: Relevance
“…However, only 5% of reads mapped to piRNAs. Other studies have also reported a minority of piRNAs in mature mammalian sperm, despite representing a considerable proportion in immature sperm in the testes and throughout spermatogenesis 15 . It has been proposed that dissociation of piRNA complexes that contribute to mRNA inactivation and remodeling in late spermiogenesis may render its associated piRNAs vulnerable to nuclease-mediated degradation 55 .…”
Section: Sequencing Results and Gene Mappingmentioning
confidence: 92%
“…However, only 5% of reads mapped to piRNAs. Other studies have also reported a minority of piRNAs in mature mammalian sperm, despite representing a considerable proportion in immature sperm in the testes and throughout spermatogenesis 15 . It has been proposed that dissociation of piRNA complexes that contribute to mRNA inactivation and remodeling in late spermiogenesis may render its associated piRNAs vulnerable to nuclease-mediated degradation 55 .…”
Section: Sequencing Results and Gene Mappingmentioning
confidence: 92%
“…Sellem et al (2021) investigated the dynamics of bovine sperm small RNAs from spermatogenesis to final maturation and observed that sperm progressively acquires miRNAs during the epididymal transit with regional specificities [ 138 ]. Several miRNAs are involved in cell cycle regulation, spermatogenesis, or embryo development, suggesting the role of epididymal small RNAs in sperm maturation and for ejaculated sperm in embryogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…When the cytoplasm of elongated spermatids is shed at the end of spermiogenesis, the CB, and MAG, which contain PRAMEY, will also be lost from the spermatids through the cytoplasmic droplets. It is believed that the cytoplasmic droplets are released mainly in the caput segment of the epididymis during sperm transition from the testis to cauda epididymis in sperm maturation ( Branton and Salisbury, 1947 ; Cooper and Yeung, 2003 ; Zhou et al, 2018 ; Sellem et al, 2021 ). Therefore, PRAMEY may be shed into epididymal lumen fluid during maturational passage of spermatozoa.…”
Section: Discussionmentioning
confidence: 99%